The Derivatives and Bank Lending Activities. Evidence from South Africa's Banking Sector: Array - Chikwira, Collin; Balkaran , Rishidaw; Rawjee, Veena (The Journal of Accounting and Management, 2021)
The study explored the impact of derivatives usage and bank credit extension within the South African banking industry from 1996 through to the end of 2017. The system generalised method of moments (GMM) estimation technique with dynamic panel data model was used.The GMM is robust in controlling for endogeneity, unobserved heterogeneity,autocorrelation and dynamic panel bias. The study revealed that derivatives positively influence lending to both the private and public sectors in South Africa. The is statistically indications that South African banks hedge credit risk, interest rate risk and cash flow risk in order to generate more revenue so that they can lend more.